6000-year Chironomid record of composite sediment core SONK_11_D from Son Kol, Kyrgyzstan, Central Asia - Andreas Laug (PANGAEA, 2019)
A 173.5 cm composite sediment core featuring the last 6000 years from the Central Asian lake Son Kol has been studied on its chironomid assemblages, showing two abrupt changes in species group composition.